ORGANIZATION OF EDUCATIONAL WORK BY THE GENERAL STAFF OF THE ARMY OF THE UKRAINIAN PEOPLE’S REPUBLIC IN THE CAMPS OF INTERNED UKRAINIAN SOLDIERS IN POLAND, 1921. - Sribnyak, Ihor (Educological discourse, 2022)
The article highlights the specifics of the activities of the cultural and educational department (board) of the General Staff of the Army of the Ukrainian People’s Republic, the activities of whose staff developed normative and instructive documents, that allowed to properly organize the work of divisional (camp) cultural and educational departments. It was established that the organization of general education of interned soldiers of the UPR Army in the camps was always marked by great difficulties, as a result of which the work of most camp educational courses and schools was irregular, but gave its positive signs. It was also very important that the general educational work in the camps was combined with a set of measures designed to strengthen the foundations of the military’s conscious understanding of state needs and consistent defense of national ones – for which Ukrainian studies courses were organized in all parts of the UPR Army. One of the main achievements of educational work was the elimination (during 1921) of illiteracy among the Cossacks of the Army of the Ukrainian People’s Republic, which was achieved through the daily efforts of the organizers in the camps. Members of public organizations of internees (student and senior communities) also contributed to the intensification of educational work in the camps. They considered it their patriotic duty to carry out such work.. However, it should be noted that the success of educational work in the camps was mostly due to the American charitable organization YMSA, which generously sponsored the vast majority of educational needs of campers. These contributions greatly enabled the work of various camp educational centers, which allowed internees to fill their camp existence with constructive content and adapt to the difficult conditions of stay in exile. The most important thing was that it created favorable opportunities for the campers to continue their education, as well as made it easier for them to master one or more civilian specialties – which ultimately greatly facilitated the employment process after the liquidation of the camps.